Option pricing : different approaches to black-Scholes and Heston models with empirical tests. - Lu, Xi. (2012)
In the past four decades, derivative markets have become increasingly important in the world of finance and investment. Various financial models have been introduced with the development of modern option pricing system. Among them, Black-Scholes model and Heston model are, perhaps, two of the most widely recognized methods for valuing options.